Angelfire ebook - Moulton, Courtney Allison (Angelfire, 2011)
First there are nightmares. Every night Ellie is haunted by terrifying dreams of monstrous creatures that are hunting her, killing her. Then come the memories. When Ellie meets Will, she feels on the verge of remembering something just beyond her grasp. His attention is intense and romantic, and Ellie feels like her soul has known him for centuries. On her seventeenth birthday, on a dark street at midnight, Will awakens Ellie's power, and she knows that she can fight the creatures that stalk her in the grim darkness. Only Will holds the key to Ellie's memories, whole lifetimes of them, and when she looks at him, she can no longer pretend anything was just a dream. Now she must hunt. Ellie has power that no one can match, and her role is to hunt and kill the reapers that prey on human souls. But in order to survive the dangerous and ancient battle of the angels and the Fallen, she must also hunt for the secrets of her past lives and truths that may be too frightening to remember.